New fossil woods from lower Cenozoic volcano‐sedimentary rocks of the Fildes Peninsula, King George Island, and the implications for the trans‐Antarctic Peninsula Eocene climatic gradient. (20th June 2019) - Oh, Changhwan; Philippe, Marc; McLoughlin, Stephen; Woo, Jusun; Leppe, Marcelo; Torres, Teresa; Park, Tae‐Yoon S.; Choi, Han‐Gu
Abstract: Ten embedded fossil logs sampled in situ from the middle Eocene volcano‐sedimentary rocks close to Suffield Point in the Fildes Peninsula, King George Island, Antarctica, are assigned to Protopodocarpoxylon araucarioides Schultze‐Motel ex Vogellehner, Phyllocladoxylon antarcticum Gothan, Agathoxylon antarcticum (Poole & Cantrill) Pujana et al ., A .  pseudoparenchymatosum (Gothan) Pujana et al . and an unidentified angiosperm wood. Differences in the taxonomic representation and growth‐ring characters of the Eocene woods on King George Island and coeval assemblages from Seymour Island, on the western and eastern sides of the Antarctic Peninsula respectively, are interpreted to result from environmental and climatic gradients across the Peninsula Orogen during the early Palaeogene. In particular, a precipitation gradient inferred across the Peninsula at that time might have been induced by a rain‐shadow effect.